Description and Study of the Extent of the Species of (Hyalomma dromedarii) Ticks Among Camels in The City of Sirte, Libya - Ahmed Al-Mashai (AlQalam Journal of Medical and Applied Sciences, 2025)
The presence of external parasites, such as ticks, is of concern as they are considered pathogens and act as vectors for diseases from one animal to another. This has a detrimental effect on the health of the animals concerned and can also harm meat production. These proteins have been identified in a variety of species, including the camel tick, which is the focus of this study. The objective of this study is twofold: firstly, to ascertain the extent of infection of camels in Sirte City, Libya, and its suburbs with Hyalomma ticks; and secondly, to isolate and study the morphology of this species of tick. The present study was conducted from October to December 2024. In the present study, a total of 162 camels residing in the suburbs of Sirte, Libya, were the subject of a comprehensive examination. Tick samples collected from infected camels were preserved in 70% ethanol and transferred to the Zoology Laboratory, Faculty of Science, University of Sirte. Following a thorough examination with the naked eye and under a microscope, the subjects were described and photographed. The results indicated that 105 camels were infected with Hyalomma dromedarii, out of a total of 162 camels that were examined. The male Hyalomma dromedarii is smaller than the female, and the scutum covers the entire dorsal surface of the body, while the female is flattened in shape, and the scutum covers only the anterior part of the dorsal surface of the body. Out of a total of 162 camels examined in the suburbs of Sirte, the results showed that 105 camels were infected with hard ticks of the Hyalomma dromedarii species.